FGFR-mediated ERK1/2 signaling contributes to mesendoderm and definitive endoderm formation in vitro - Lau, Hwee Hui; Amirruddin, Nur Shabrina; Loo, Larry Sai Weng; Chan, Jun Wei; Iich, Elhadi; Krishnan, Vidhya Gomathi; Hoon, Shawn; Teo, Adrian Kee Keong (iScience, 2023)
The differentiation of human pluripotent stem cells into the SOX17+ definitive endoderm (DE) germ layer is important for generating tissues for regenerative medicine. Multiple developmental and stem cell studies have demonstrated that Activin/Nodal signaling is the primary driver of definitive endoderm formation. Here, we uncover that the FGF2-FGFR-ERK1/2 signaling contributes to mesendoderm and SOX17+ DE formation. Without ERK1/2 signaling, the Activin/Nodal signaling is insufficient to drive mesendoderm and DE formation. Besides FGF2-FGFR-mediated signaling, IGF1R signaling possibly contributes to the ERK1/2 signaling for DE formation. We identified a temporal relationship between Activin/Nodal-SMAD2 and FGF2-FGFR-ERK1/2 signaling in which Activin/Nodal-SMAD2 participates in the initiation of mesendoderm and DE specification that is followed by increasing activity of FGF2-FGFR-ERK1/2 to facilitate and permit the successful generation of SOX17+ DE. Overall, besides the role of Activin/Nodal signaling for DE formation, our findings shed light on the contribution of ERK1/2 signaling for mesendoderm and DE formation. [Display omitted] •FGF2 potentiates mesendoderm and DE formation through FGFR2 and ERK1/2 signaling•ERK1/2 signaling is involved in cell cycle process•IGF1R- but not IR-mediated ERK1/2 signaling also contributes to DE formation•Increased pSMAD2 on inhibition of FGFR2-ERK1/2 signaling fails to direct DE formation Biological sciences; Molecular biology; Developmental biology; Embryology